Variation in sunscreen compounds (mycosporine‐like amino acids) for marine species along a gradient of ultraviolet radiation transmission within doubtful sound, New Zealand - Miles D. Lamare; Michael P. Lesser; Mike F. Barker; Thomas M. Barry; Kate B. Schimanski (New Zealand Journal of Marine and Freshwater Research, 2004)
We examined the response of four species of New Zealand marine algae ( Ecklonia radiata, Apophlaea lyallii, Rhodymenia spp., Ulva lactuca ) and a sea urchin ( Evechinus chloroticus ) to spatial variation in ultraviolet radiation (UV‐R) by examining the concentration of UV‐R absorbing compounds known as mycosporine‐like amino acids (MAAs). The purpose was to understand how, and the degree to which, local marine species could potentially respond to any future increases in incident UV‐R in the New Zealand marine environment. The research was undertaken in Doubtful Sound, where we observed a gradient of water column UV‐R transmission along the 40 km length of the fiord. We examined spatial differences in MAAs along the UV‐B gradient in the macrophytes and temporal changes in MAAs in sea urchin gonads. Among the algae, thallus MAA concentrations (nmol mg –1 protein) ranged from 12.5 to 87.8 in E. radiata , from 433.1 to 1446.4 in A. lyallii , 12.7 to 103.4 in Rhodymenia spp., but were not detected in U. lactuca . For E. chloroticus , gonadal MAA concentrations ranged from 83.9 to 224.3 nmol mg –1 protein spatially, and over the year from 1.85 to 14.12 nmol mg –1 dry weight (DW) depending on site and gametogenic cycle. Laboratory manipulations indicated that concentrations of MAAs in E. chloroticus gonads and eggs are influenced by diet. MAA concentration could be correlated with UV‐B intensities in two of the algal species. E. chloroticus MAA concentrations could also be correlated with UV‐B transmission, which we concluded was a reflection of the greater ingestion and accumulation of MAA‐rich macrophytes at those sites where higher ambient UV‐R induced greater MAA concentrations to occur in the algae. Given this, we suggest that one response of marine species to increases in UV‐B would be an increase in the synthesis and/or accumulation of MAAs for photoautotrophs and a dietary accumulation of those MAAs in E. chloroticus , an important herbivore in this system.